Combination of geostatistics and drastic model in assessing groundwater vulnerability to nitrate contamination [electronic resource] - Rohazaini Muhammad Jamil, 1984-; Mohamad Nor Said, supervisor; Mohd. Nadzri Md. Reba (2014)
Thesis (Sarajana Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2014